The l-rhamnose-dependent regulator RhaS and its target promoters from Escherichia coli expand the genetic toolkit for regulatable gene expression in the acetic acid bacterium Gluconobacter oxydans - Fricke, Philipp Moritz; Gries, Mandy Lynn; Mürköster, Maurice; Höninger, Marvin; Gätgens, Jochem; Bott, Michael; Polen, Tino (Frontiers in Microbiology, 2022)
For regulatable target gene expression in the acetic acid bacterium (AAB) Gluconobacter oxydans only recently the first plasmids became available. These systems solely enable AraC- and TetR-dependent induction. In this study we showed that the L-rhamnose-dependent regulator RhaS from Escherichia coli and its target promoters PrhaBAD, PrhaT, and PrhaSR could also be used in G. oxydans for regulatable target gene expression. Interestingly, in contrast to the responsiveness in E. coli, in G. oxydans RhaS increased the expression from PrhaBAD in the absence of L-rhamnose and repressed PrhaBAD in the presence of L-rhamnose. Inserting an additional RhaS binding site directly downstream from the –10 region generating promoter variant PrhaBAD(+RhaS-BS) almost doubled the apparent RhaS-dependent promoter strength. Plasmid-based PrhaBAD and PrhaBAD(+RhaS-BS) activity could be reduced up to 90% by RhaS and L-rhamnose, while a genomic copy of PrhaBAD(+RhaS-BS) appeared fully repressed. The RhaS-dependent repression was largely tunable by L-rhamnose concentrations between 0% and only 0.3% (w/v). The RhaS-PrhaBAD and the RhaS-PrhaBAD(+RhaS-BS) systems represent the first heterologous repressible expression systems for G. oxydans. In contrast to PrhaBAD, the E. coli promoter PrhaT was almost inactive in the absence of RhaS. In the presence of RhaS, the PrhaT activity in the absence of L-rhamnose was weak, but could be induced up to 10-fold by addition of L-rhamnose, resulting in a moderate expression level. Therefore, the RhaS-PrhaT system could be suitable for tunable low-level expression of difficult enzymes or membrane proteins in G. oxydans. The insertion of an additional RhaS binding site directly downstream from the E. coli PrhaT –10 region increased the non-induced expression strength and reversed the regulation by RhaS and L-rhamnose from inducible to repressible. The PrhaSR promoter appeared to be positively auto-regulated by RhaS and this activation was increased by L-rhamnose. In summary, the interplay of the L-rhamnose-binding RhaS transcriptional regulator from E. coli with its target promoters PrhaBAD, PrhaT, PrhaSR and variants thereof provide new opportunities for regulatable gene expression in G. oxydans and possibly also for simultaneous L-rhamnose-triggered repression and activation of target genes, which is a highly interesting possibility in metabolic engineering approaches requiring redirection of carbon fluxes.